Sperm And Egg Quality In Catla And Rui Between Spawning Seasons In Bangladesh - Hasan, Mahmud; Rahman, Md Mofizur; Hossain, Anwar; Rabbane, Md Golam (Journal of the Asiatic Society of Bangladesh, Science, 2014)
Sperm and egg quality of catla Catla catla and rui Labeo rohita were investigated in Brahmaputra and Sarker Hatchery, Mymensingh, Bangladesh over two spawning seasons as early (March to May) and peak (June to August ). In both hatcheries, catla and rui produced nearly 90% motile sperms as well as higher sperm concentration (catla: Brahmaputra hatchery. 2533.33 ± 119.65 million mL-1 and Sarker hatchery, 2658.89 ± 76.55 million mL-1; rui: Brahmaputra hatchery, 2856.67 ± 67.57 million mL-1 and Sarker hatchery, 2811.67 ± 51.90 million mL'1), seminal pH (catla: Brahmaputra hatchery, 7.41 ± 0.06 and Sarker hatchery, 7.41 ± 0.06; rui: Brahmaputra hatchery, 7.39 ± 0.05 and Sarker hatchery, 7.35 ± 0.05) and fertilizability in catla were 88% and In rui 92% in both hatcheries in the peak season. The occurrence of opaque eggs in catla and rui was 12% and 8% in both hatcheries in the peak season, respectively. The present study points to the fact that the quality of fish sperm and egg depends on seasons Asiat. Soc. Bangladesh, Sci. 40(2): 231-241, December 2014